Illustrated encyclopedia of the earth - Luhr, James F. (Dorling Kindersley, 2011)
Offers an exploration of planet Earth. From the fiery mass of the Earth's core to the tip of the highest ice-capped mountain, this title helps you explore various aspects of our planet in photographic detail. It helps you visit 400 of the tallest, longest, widest, most significant and most unusual physical features on Earth